Gifts, Surveillance, and Frustrated Imagined Communities: Global Christian Aid and Local Inequalities in Child Sponsorship in the Ecuadorian Highlands - María Moreno Parra (Íconos)
In this paper I examine how an indigenous development organization that works with an international evangelica0l funding agency participates in the ‘government of populations’ through the system of child sponsorship. On the one hand, the indigenous organization is subjected to the verticality of its funding agency through processes of legibility and accountability that ensure the correct operation of child sponsorship. On the other, the indigenous organization is a subject governing specific populations because it controls the children and its families. Furthermore, I explore how practices linked to child sponsorship—such as gifts sent by sponsors and the correspondence between sponsors and children—are intended to build personal connections in a Christian community that transcends geographical, economic, and social boundaries, but end up amplifying inequality, especially at the local level.